The Knowledge of Hypertension Patients about Stroke Risk and Treatment at Santa Elisabeth Hospital Medan - Lindawati F. Tampubolon; Lilis Novitarum; Vina Yolanda Sigalingging; Sukemi Saragih (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Hypertension substantially increases the risk of developing secondary conditions, including stroke, renal disease, coronary heart disease, and heart failure. Early management is therefore essential to prevent complications and adverse outcomes. Evidence indicates that untreated hypertension contributes to approximately 60% of stroke cases. Public knowledge regarding hypertension-related complications remains limited, and many individuals are unable to identify early signs of stroke the most common complication associated with hypertension. This study aimed to assess the knowledge of hypertensive patients regarding stroke risk and management at Santa Elisabeth Hospital Medan in 2024. A descriptive research design was employed. The sample consisted of 67 hypertensive patients attending the outpatient clinic, selected through purposive sampling. Data were presented using frequency distribution tables. The findings revealed that 52.2% of respondents demonstrated poor knowledge, 32.8% had moderate knowledge, and only 14.9% showed good knowledge regarding stroke risk and management. These results underscore the need for patients to adopt healthier lifestyles and for the hospital to strengthen educational efforts by providing more engaging and interactive learning materials for patients and their families.